Evaluation of Chitosan-Derived Mixed-Matrix Membranes as Potential Separators in Bioelectrochemical Systems - Santiago Alvear Méndez; Raúl Bahamonde Soria; Daniel Arboleda; Carlos Cevallos; Chistian Alcivar; Henry Pupiales; Patricia Luis (Chemistry Proceedings, 2024)
Bioelectrochemical systems are energy-efficient devices that transform chemical energy into electrical energy or synthesize products of interest. These technologies make use of Nafion membranes that function as proton exchangers; however, these separators have some problems, such as fouling. Therefore, this research explores mixed-matrix membranes of chitosan and chitosan derivatives to determine their antimicrobial, anti-fouling, chemical stability and high-water retention properties. The results showed that these membranes could be good candidates to be used as separators in bioelectrochemical systems.